STRATEGI KOMUNIKASI DALAM PENGELOLAAN DAN PENATAAN KAWASAN WISATA KUTA MENJELANG MOTOGP 2023 - Yasa, I Komang Widya Purnama (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2023)
The communication strategy for managing and structuring the Kuta tourist area ahead of MotoGP 2023 will provide valuable insight into the role of local government in facing the challenges and opportunities faced in holding this international sporting event. The research method uses a qualitative descriptive approach with primary data sources obtained from local government, residents, and tourists. This research discusses the strategies of policymakers in preparing for international events. The analysis carried out in this research is regarding the role of MotoGP in increasing tourism in the Kuta area, residents as part of the success of the MotoGP event, communication strategies in management and arrangement of the Kuta tourism area, and implications for management of the Kuta tourism area. This matter's importance was discussed to create conducive comfort for tourists during MotoGP 2023.